Integrasi Model dan Metode Perencanaan Pendidikan Islam dalam Meningkatkan Efektivitas Manajemen Pendidikan - Kurniati, Yeli; gusmira, yessy; filko, ayani; asmendri, asmendri; milyasari, milyasari (LPPM UM Metro, 2025)
Educational planning is a structured process that guides and evaluates educational implementation effectively and efficiently. This study aims to analyze the integration of planning models and methods in Islamic education to improve management effectiveness in the Industrial Revolution 4.0 era. Using a library research method, this paper examines several educational planning models such as the comprehensive model, costing model, PPBS, and target setting, as well as analytical methods including input–output, econometric, and projection methods. The results show that integrated application of models and methods in educational planning strengthens institutional performance, resource allocation, and curriculum relevance to global challenges. Moreover, the study emphasizes that effective planning in Islamic education must combine managerial, spiritual, and technological dimensions to achieve educational excellence.